How to perform lung ultrasound in pregnant women with suspected COVID‐19. (1st May 2020) - Moro, F.; Buonsenso, D.; Moruzzi, M. C.; Inchingolo, R.; Smargiassi, A.; Demi, L.; Larici, A. R.; Scambia, G.; Lanzone, A.; Testa, A. C.
ABSTRACT: Under certain circumstances, such as during the current COVID‐19 outbreak, pregnant women can be a target for respiratory infection, and lung examination may be required as part of their clinical evaluation, ideally while avoiding exposure to radiation. We propose a practical approach for obstetricians/gynecologists to perform lung ultrasound examination, discussing potential applications, semiology and practical aspects, which could be of particular importance in emergency situations, such as the current pandemic infection of COVID‐19. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd.